2018
DOI: 10.1002/cphc.201701209
|View full text |Cite
|
Sign up to set email alerts
|

Force‐Induced Catastrophes on Energy Landscapes: Mechanochemical Manipulation of Downhill and Uphill Bifurcations Explains the Ring‐Opening Selectivity of Cyclopropanes

Abstract: The mechanochemistry of ring-opening reactions of cyclopropane derivatives turns out to be unexpectedly rich and puzzling. After showing that a rare so-called uphill bifurcation in the case of trans-gem-difluorocyclopropane turns into a downhill bifurcation upon substitution of fluorine by chlorine, bromine, and iodine in the thermal activation limit, the dichloro derivative is studied systematically in the realm of mechanochemical activation. Detailed exploration of the force-transformed potential energy surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The product distribution is likely the result of a post-transition-state bifurcation on the force-modified potential energy surface. This phenomenon has been recently observed in other mechanochemical transformations, 33,34 and might be more common than anticipated. Interestingly, the shape of the force-modified PES can be altered to favour a particular dissociation pathway by tuning the electronic properties of the mechanophore.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The product distribution is likely the result of a post-transition-state bifurcation on the force-modified potential energy surface. This phenomenon has been recently observed in other mechanochemical transformations, 33,34 and might be more common than anticipated. Interestingly, the shape of the force-modified PES can be altered to favour a particular dissociation pathway by tuning the electronic properties of the mechanophore.…”
Section: Discussionsupporting
confidence: 69%
“…6d). The emergence of a post-TS bifurcation in a force-modified PES has been recently observed in other mechanophores, 33,34 and could be a common phenomenon in mechanochemical transformations. Since the minor homolytic pathway is not observed when the importance of the heterolytic pathway decreases (Fig.…”
Section: Dissociation Mechanismmentioning
confidence: 67%
“…Interestingly, other studies of cyclobutane mechanochemical cycloreversion by Craig 28 and Wang 15 groups reported higher fractions of stereochemical inversion. The stereochemical distribution of the mechanochemically generated diene can be ascribed to the instability of the diradical transition state upon the first bond scission and dynamic effect, 29,30 and warrants comprehensive computational studies. 22% and 28% mechanophore activation per scission cycle was achieved for P1-H and P2-H , respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They further showed the impact of halogen substitution on the thermally activated ring-opening process followed by halogen migration of (2S,3S)-1,1-dihalo-2,3-dimethylcyclopropanes in the case of F, Cl, Br and I distribution. 141 Surprisingly, the direction of halogen migration in the case of disrotatory ring-opening was qualitatively different for the difluorinated cyclopropane compared with the homologous Cl, Br and I species. For gDFC E-isomer, the decision was governed by an uphill bifurcation followed by two separate transition states for each migration direction, whereas the disrotatory transition state was first surmounted in the other three cases followed by a downhill bifurcation into the disrotatory products.…”
Section: Mechanistic Considerationsmentioning
confidence: 94%